PECULIARITIES OF ACCOUNTING FOR OWN CAPITAL IN MODERN ECONOMIC CONDITIONS - Savinova Galina Anatolevna (Modern American Journals, 2025)
In this article, we will focus on the key aspects related to accounting for a company's equity in a modern economy. Our goal is to find ways to more accurately and transparently reflect equity in accordance with International Financial Reporting Standards (IFRS). The analysis shows that effective management and accounting of equity are fundamental factors ensuring financial stability, attractiveness to investors and long-term development of the company. In the era of digitalization, the emergence of complex financial instruments, the increasing role of intellectual capital and the growing requirements for reporting on sustainable development, the methodology of accounting for equity requires constant improvement. In the course of our research, we have studied in detail the processes of digitization, complex financial instruments, as well as the growing importance of intellectual capital and the impact of asset revaluation on capital. In the course of the study, reasonable conclusions were drawn and practical recommendations were developed aimed at increasing the transparency and reliability of the direct investment account. These recommendations are aimed at ensuring financial stability, improving investment attractiveness, and improving the efficiency of corporate governance.
Keywords: Own capital, own funds, accounting, international financial reporting standards (IFRS), digitalization, financial stability, investment attractiveness, intellectual capital, complex financial instruments, internal control, accounting policy.